2014
DOI: 10.1556/avet.2013.060
|View full text |Cite
|
Sign up to set email alerts
|

Skin and skeletal system lesions of european pond turtles (Emys orbicularis) from natural habitats

Abstract: Water pollution is known to play an important role in the pathogenesis of plastron, carapace and skin diseases of turtles. In this study, a total of 150 European pond turtles (Emys orbicularis) of different age and both sexes, originating from natural habitats in Serbia, were examined for morphological changes of the skin, plastron, carapace and skeletal system. The turtles were taken out from their natural habitats in Lake Ludas, Lake Palic and Lake Tresetiste. After artificial hibernation, they were subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
(11 reference statements)
1
13
0
4
Order By: Relevance
“…Both the wild animals and the specimens from the breeding facility of the Xambioá Indigenous Land appeared to be healthy and without visible anomalies. However, in the breeding facility of the Praia Alta Ranch, there were animals with soft shells and a relatively high amount of skin ulcerations, most likely caused by fungi and bacteria (ALEKSIĆ-KOVAČEVIĆ et al, 2014). The presence of unidentified slime material on the shells of the animals of the Praia Alta Ranch was also observed.…”
Section: Resultsmentioning
confidence: 97%
“…Both the wild animals and the specimens from the breeding facility of the Xambioá Indigenous Land appeared to be healthy and without visible anomalies. However, in the breeding facility of the Praia Alta Ranch, there were animals with soft shells and a relatively high amount of skin ulcerations, most likely caused by fungi and bacteria (ALEKSIĆ-KOVAČEVIĆ et al, 2014). The presence of unidentified slime material on the shells of the animals of the Praia Alta Ranch was also observed.…”
Section: Resultsmentioning
confidence: 97%
“…A similar phenomenon has been described for rats, whereby exposure to Cd and Pb led to disturbances in bone structure connected with an early stage of osteoporosis in these young individuals (Duranova et al 2014; Lu et al 2014). As well, studies of European pond turtles at three natural locations differing in their degree of pollution showed that nutrient-rich (nitrogen and phosphorus) and polluted waters exert a major impact on the pathogenesis of plastron and carapace including necrosis and osteoporosis (atrophy of bone tissue) (Aleksić-Kovačević et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Due to the wet habitat, a number of bacteria can invade the organism via mechanical lesions of the shell [16] and mycoses were often described to be the cause of shell necroses [17,18]. The alterations in haematocrit, number of erythrocytes and haemoglobin concentration, basophilia, eosinophilia, heterophilia, and azurophilia can be regarded as typical of turtles suffering from chronic infections, undernourishment and chronic stress [19].…”
Section: Discussionmentioning
confidence: 99%